Modified Technique for Scleral-Sutured Fixation with the Double Knots Technique for Posterior Chamber Intraocular Lens: Short-Term Observation - Zhizhong Wu; Caijuan Liu; Yanhui Xu; Wei Dong; Zhimin Chen (Journal of Ophthalmology)
Purpose. To evaluate the short-term safety and efficacy of a novel approach of utilizing the 9-0 looped polypropylene suture with double knots buried into the scleral groove and the scleral tunnel to minimize the risk of the suture erosion and suture knot exposure. Design. Clinical-based retrospective study. Methods. Records of consecutive patients who had anterior vitrectomy and scleral-fixated posterior chamber intraocular lens (IOL) implantation between July 2018 and April 2020 with a minimum follow-up of 3 months were reviewed. Results. This study enrolled a total of 21 eyes from 20 patients (15 male). These patients had a mean age of 58.52 ± 8.55 years and were followed for an average of 1.08 ± 0.58 years postoperatively. Best-corrected visual acuity (BCVA) improved from a preoperative mean of 0.43 ± 0.41 logMAR to a significantly higher mean 3-month postoperative value of 0.09 ± 0.21 logMAR (Z = -3.35, p<0.01). There were no statistical differences between the preoperative and postoperative corneal endothelial cell density (p=0.71). The postoperative complications included transient increased intraocular pressure in 5 eyes (24%). No other complications were detected during the follow-up. Conclusions. The modified technique proposed is a safe, effective, and reliable approach resulting in good visual outcomes. Our procedure might have the potential benefit to avoid suture-related complications in scleral-fixated IOL implantation. Trial registration. Retrospective case series study, not applicable.